The impact of adjuvant hysterectomy on survival outcomes of patients with locally advanced cervical cancer: A network meta-analysis. Issue 1 (January 2022) - Pergialiotis, Vasilios; Bellos, Ioannis; Douligeris, Athanasios; Thomakos, Nikolaos; Rodolakis, Alexandros; Haidopoulos, Dimitrios
Abstract: Background and objectives: Various articles have addressed the impact of hysterectomy on survival outcomes of patients with locally advanced cervical cancer (LACC). This study was designed to evaluate whether treatment modalities that include hysterectomy as an option for the treatment of LACC patients are superior to standard chemo-radiotherapy. Methods: Literature search was performed using the Medline, Scopus, Cochrane Central Register of Controlled Trials (CENTRAL), Web of Science and Clinicaltrials.gov databases. Observational (prospective and retrospective) and randomized trials that included adjuvant hysterectomy in at least one treatment group. A network meta-analysis was carried out in R 3.4.3 using the pcnetmeta package, which uses a Bayesian hierarchical model. The credibility of evidence was appraised with the Confidence In Network Meta-Analysis (CINeMA) tool. Results: Overall, 14 studies were included in the present systematic review that involved 2302 patients with LACC. Every potential combination of external beam radiotherapy, intracavitary brachytherapy, chemotherapy and surgery was considered to be eligible for inclusion. The results of the network meta-analysis suggested that the various treatment alternatives did not differ in terms of survival outcomes. Furthermore, the qualitative analysis revealed that hysterectomy was accompanied by considerable perioperative morbidity; therefore, rendering its addition to the treatment scheme of LACC patients inappropriate. Conclusions: Patients with LACC do not seem to benefit substantially by the addition of hysterectomy to standard chemo-radiotherapy. Moreover, the operation is accompanied by substantial perioperative morbidity, thus, its implementation in clinical practice should be avoided.